Identification of a Novel Antimicrobial Peptide From the Ancient Marine Arthropod Chinese Horseshoe Crab, Tachypleus tridentatus - Wang, Wei-Feng; Xie, Xiao-Yong; Huang, Yan; Li, Yin-Kang; Liu, Hong; Chen, Xiu-Li; Wang, Huan-Ling (Frontiers in Immunology, 2022)
Humoral immunity is the first line of defense in invertebrate immune system, and antimicrobial peptides play an important role in this biological process. A novel antimicrobial peptide, termed Tatritin, was identified and characterized in hemolymph of Chinese horseshoe crab, Tachypleus tridentatus, infected with Gram-negative bacteria via transcriptome analysis. Tatritin was significantly induced by bacterial infection in hemolymph and gill. The preprotein of Tatritin consists of a signal peptide (21 aa) and a mature peptide (47 aa) enriched by cysteine. The putative mature peptide was 5.6 kDa with a theoretical isoelectric point (pI) of 9.99 and showed a α-helix structure in the N-terminal and an anti-parallel β-sheet structure in the cysteine-stabilized C-terminal region. The chemically synthesized peptide of Tatritin exhibited a broad spectrum of antimicrobial activity against Gram-negative and Gram-positive bacteria and fungi. Furthermore, Tatritin may recognize and inhibit pathogenic microorganisms by directly binding to LPS, DNA and chitin. In addition, administration of Tatritin reduced the mortality of zebrafish after bacterial infection. Due to its broad-spectrum antimicrobial activity in vivo and in vitro and the sensitivity to drug-resistant bacterial strains, Tatritin peptide can be used as a new type of drug for infection treatment or as an immune enhancer in animals.